The time for Futurism - Bortulucce, Vanessa Beatriz (PORTO ARTE: Revista de Artes Visuais, 2016)
This article aims to reflect on the legacy of Italian Futurism in 20th-century art and culture, as well as to discuss over how aesthetics and futuristic ideology permeate the post-modern and globalized scenario of the present days. In seeking to demonstrate how the futuristic experience contributed to the development of a poetics of contemporary art, we intend to launch a look at Futurism as an aesthetic of time, a motion turned into a kind of archetype of future artistic experiences.